A complexity-based approach to batterer intervention programmes (2014)
This paper was aimed at providing opinion by adopting a complexity-based approach to coordinating nursing science and psychology concerning psycho-educational intervention for batterers regarding their partner or ex-partner. Improving both disciplines’ interrelationship should facilitate implementing relevant action, thereby engendering motivation for change in participants and modifying sexist attitudes and beliefs. The document has analyzed the importance of coordinating scientific disciplines’ action and defined guidelines for an approach involving intervention as well as highlighting implications for practice and research.